2019
DOI: 10.3126/njh.v16i2.26310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular systolic function by Myocardial Deformation Imaging in asymptomatic HIV patients

Abstract: Background and Aims: Despite improvements in clinical care, evidence from both industrialized and developing countries indicates that the prevalence of subclinical cardiac dysfunction in individuals with well-controlled HIV infection may approach 50% and represent a newly recognized comorbid condition. The aim of our study was to reveal abnormalities in cardiac function using conventional transthoracic echocardiography and left ventricular strain imaging in HIV infected patients without cardiovascular disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, the HIV population had significantly lower mean global longitudinal strain values (GLS). Furthermore, studies have shown that impaired GLS correlated with decreased CD4 counts ( 19 , 20 ).…”
Section: Echocardiographymentioning
confidence: 99%
“…However, the HIV population had significantly lower mean global longitudinal strain values (GLS). Furthermore, studies have shown that impaired GLS correlated with decreased CD4 counts ( 19 , 20 ).…”
Section: Echocardiographymentioning
confidence: 99%